STUDI FERMENTASI UNTUK MODIFIKASI PATI SAGU OLEH BAKTERI ASAM LAKTAT DENGAN METODE PERENDAMAN - Tuahta, Beltaser; Restuhadi, Fajar; Pato, Usman (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The role of wheat flour is very important in the food industry in Indonesia. Wheat flour is still imported by Indonesia which reaches three million tons / year. One way to reduce the import of wheat flour is by the utilization of local sago.The purpose of this study was to obtain the effect of fermentation time for modification of sago starch by Lactic Acid Bacteria by the soaking method. This research has been conducted in the Laboratory of Agricultural Technology and Laboratory of Agricultural Product Analysis, University of Riau. This research was conducted experimentally using a Completely Randomized Design with 5 treatments and 3 replications. The results obtained show that sago starch fermentation significantly affected the water, ash and amylose contents, viscosity, and descriptive assessment of the aroma, color and flavor. However, there was no significantly affect on the pH and total Lactic Acid Bacteria. Key words:sago starch, fermentation, lactic acid bacteria